Analysis and comparison of training load between two groups of women's artistic gymnasts related to the perception of effort and the rating of the perceived effort session - Trucharte, P.; Grande, I. (Science of Gymnastics Journal, 2021)
The aim of this study was to assess the internal training load in female artistic gymnastics through subjective perception of effort (PSE) by calculating the sRPE variable and different associated variables. Ten gymnasts participated (age: 14.4 ± 2.9 years; height: 1.5 ± 0.1 m; mass: 43.3 ± 12.2 kg) and were divided into two groups according to their competitive level and weekly training volume: High Level Gymnasts (HLG) and Medium Level Gymnasts (MLG). The PSE of each gymnast was recorded daily for four weeks after the end of each training block. The HLG group recorded a significantly higher RPE and sRPE value in the specific physical preparation (SST) and in the parallel technical training (UB) contents (p < 0.05) compared to MLG. Statistically significant differences were also obtained from the registered mean values of RPE and sRPE when comparing training content. Furthermore, a direct relationship between volume and workload was observed. Finally, the variables associated with injury risk control provided relevant information to determine that the HLG group had a higher risk of injury than the MLG group. Therefore, the sRPE has been a useful tool to assess the internal training load in women's artistic gymnastics. Such information may help quantify the load in this sport in the future.